Influence of traditional dietary practices on dental caries: a study of Changal among the Hmar tribe - Joycee Lalnunsiem; Dhruba Kumar Limbu (International Journal Of Community Medicine And Public Health, 2026)
Background: Among the Hmar tribes of northeast India, traditional dietary practices involving the consumption of Changal continue to be widely prevalent; however, their impact on dental caries has received little scientific attention. Therefore, the present study was undertaken to investigate the potential impact of traditional dietary practices and their associations with dental caries among the Hmar tribe of Cachar district of Assam. Methods: A comparative cross-sectional study was conducted among 200 Hmar participants. The samples consisted of 100 consumers and 100 non-consumers, both male and female. Statistical analysis was performed using chi-square test to evaluate the association between Changal consumption and the prevalence of dental caries. Results: In the present study, age was not significantly associated with dental caries (p>0.05). The prevalence of dental caries among non-consumers of Changal individuals was high (52% males and 62% females). However, lower prevalence of dental caries was observed among those who consumed Changal daily (p